Getting heard? How employees learn to gain senior management attention in inclusive strategy processes - Splitter, V; Seidl, D; Whittington, R (Wiley, 2024)
Research Summary Recent trends toward inclusive strategy processes raise the issue of how employees acquire the discursive competence necessary to gain senior management attention. Building on the emergent dynamic attention-based view's (DABV) emphasis on communicative interaction, we ethnographically track an inclusive strategy process in a large insurance company. We find that employees typically failed to gain CEO attention because they lacked the discursive competence to integrate their operational knowledge with the CEO's corporate themes. Employees acquired this competence by both experiential and vicarious learning. The CEO promoted employee learning more effectively by specific coaching than by generic coaching. We contribute primarily to the DABV by showing how interactions are sites for learning as well as communications and that communication channels can be both expandable and transparent.